2016
DOI: 10.1177/1082013215624807
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the isothermal inactivation curves of Listeria innocua CECT 910 in a vegetable beverage under low-temperature treatments and different pH levels

Abstract: Thermal inactivation kinetics of Listeria innocua CECT 910 inoculated in a vegetable beverage at three pH conditions (4.25, 4.75, and 5.20), four levels of temperature (50, 55, 60, 65℃), and different treatment times (0-75 min) were obtained. Survival curves did not follow a log-linear relationship and consequently were fitted to various mathematical models: Weibull, Geeraerd, Cerf with shoulder, and the modified Gompertz equation. Results indicated that the best model for the treatment conditions was the modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…The criteria and parameters used to compare the goodness of fit of the models were: Adjusted coefficient of multiple determinations (Adj R 2 ), Estimated Standard Deviation of the Regression Error Term ( RMSE ), and the Akaike Information Criteria for Model Selection [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The criteria and parameters used to compare the goodness of fit of the models were: Adjusted coefficient of multiple determinations (Adj R 2 ), Estimated Standard Deviation of the Regression Error Term ( RMSE ), and the Akaike Information Criteria for Model Selection [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the thermal inactivation of microorganisms by capillary method have been reported as an accurate procedure to measure heat resistance with the advantage of shorter come up times compared to other methods that could reduce thermal lag time, and the use of lower volumes with high concentrated microbial suspensions. By this method, both linear and nonlinear behaviors have been observed in survival curves attributed to differences, for example, in food substrates composition (pH, solid content, water activity, among others), strain used, temperature range, and heating method (Ferna´ndez et al, 1999;Fujikawa et al, 2000Fujikawa et al, , 2001Vega et al, 2016). In the case of linear inactivation behavior, Fairchild and Foegeding (1993) studied the heat resistance of L. monocytogenes and L. innocua M1 in skim milk; D values were determined ranging from 38.5 s at 61.8 C to 1.4 s at 69.5 C, and z values of 5.5 and 5.6 C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the generation of heat shock proteins in microbial cells during heating might be related to tailing, which is possibly the effect of a thermo-resistant subpopulation (Fujikawa et al, 2001). Vega et al (2016) studied the isothermal inactivation curves of L. innocua CECT 910 in a vegetable beverage by the capillary method where the cells were exposed to three pH levels (4.25, 4.75, and 5.20), four temperature levels (50, 55, 60, 65 C), and different exposure times (0-75 min). The modified Gompertz equation provided the best goodness-of-fit for describing the non-linear survival curves with shoulders and tails, and the temperature and time were the most influential factors affecting the final microbial load in the case of the higher temperature level (65 C), and the time in the case of the lower temperature level (50 C) tested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations